IMPLEMENTASI METODE CERTAINTY FACTOR PADA SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT ANEMIA - Reny Wahyuning Astuti; Hambali Furnawan; Wahyu Segianto (JURNAL AKADEMIKA)
Expert system to diagnose anemia is a computer-based system that is used as a tool to diagnose anemia based on the dynamic knowledge base. The knowledge base contains knowledge acquired from various sources including from the experience of experts in the field and also books related to the diagnosis of anemia were then collected into a database that is required for making a conclusion. In this system will be used methodcertainty factor. This system uses the values of the certainty of the symptoms of anemia to see the tendency ofpatients diagnosed with any type of anemia. Besides, the system will provide an explanation of the diagnosis isdone